Phytochemical Constituents and Antioxidant Activity of Sweet Basil (Ocimum basilicum L.) Essential Oil on Ground Beef from Boran and Nguni Cattle - Andrew Bamidele Falowo; Felicitas Esnart Mukumbo; Emrobowansan Monday Idamokoro; Anthony Jide Afolayan; Voster Muchenje (International Journal of Food Science)
The global meat industry is characterised by a growing interest in natural preservative additives. This study determined the effect of sweet basil (Ocimum basilicum L.) essential oil (SBEO) on colour and lipid oxidation in minced beef. The phytoconstituents of SBEO were analyzed by gas chromatography mass spectrometry. Thereafter, minced beef samples from Nguni and Boran cattle were treated with either no additives (control, C) or SBEO added at 2% (SB2), 4% (SB4), or 6% (SB6). The meat samples were aerobically packaged and stored (4 ± 1°C) for seven days for measurement of lightness (L⁎), redness (a⁎), yellowness (b⁎), hue, chroma, and lipid oxidation (acid-reactive substances, TBARS) on days 0, 4, and 7. Thirty-two bioactive compounds with reported antioxidant and antimicrobial and activities were identified in SBEO, including Estragole (41.40%), 1, 6-Octadien-3-ol, 3,7-dimethyl (29.49%), and trans-.alpha.-Bergamotene (5.32%). On days 0, 4, and 7, SB2, SB4, and SB6 had higher (P < 0.05) L⁎, a⁎, b⁎, hue, and chroma values; and on days 0 and 4 TBARS were lower (P < 0.05) in SB2 and SB4 than C and SB6. The addition of 2% and 4% SBEO improved colour and lipid oxidative stability, demonstrating potential for its use as a natural antioxidant additive in meat.